Community Health Worker's Behavior in Prevention and Treatment of Diarrhea At Home in Mothers with Toddlers - Haryani, Sri; Yusniarita, Yusniarita; Sutriyanti, Yanti; Bakara, Derison Marsinova; Buana, Chandra (JOSING: Journal of Nursing and Health, 2024)
This study aims to determine how the behavior of community health worker in preventing and treating diarrhea at home in mothers who have toddlers at home. This study used a quantitative research type with a Quasi Experiment design with an intervention group and a control group. The design used is pre-test and post-test. The results of the study obtained pre-test knowledge for the intervention and control groups at the age of cadres 57 (95%) adults, higher education 59 (98.3%), length of time as a cadre 44 (73.3%) long. Pre knowledge with p-value 0.257, post 0.000 and pre attitude 0.379 post 0.160, and pre action 0.814 post 0.603. The conclusion was that the knowledge of community health worker was good after health education was carried out and for the attitudes and actions of community health worker were not good after health education was carried out in preventing and treating diarrhea at home in mothers who with toddlers. Keywords: Knowledge, Attitude, Action, Community Health Worker, Treatment, Diarrhea